Childhood asthma prevalence and risk factors in three Eastern European countries - the Belarus, Ukraine, Poland Asthma Study (BUPAS): an international prevalence study. Issue 1 (December 2016) - Brozek, Grzegorz; Lawson, Joshua; Shpakou, Andrei; Fedortsiv, Olga; Hryshchuk, Leonid; Rennie, Donna; Zejda, Jan
Abstract Background The prevalence of asthma and other allergic diseases among children living in Eastern is not well described. Our objective was to estimate and compare the prevalence of asthma, respiratory symptoms and allergic diseases in children in Belarus, Ukraine, and Poland as well as to identify risk factors for these conditions. We also sought to profile and compare children with asthma between locations. Methods Data were collected as a part of an international, multicenter, cross-sectional study of childhood asthma: The Belarus Ukraine Poland Asthma Study (BUPAS). Subjects were children aged 7–13 years attending primary and secondary schools in the urban and surrounding rural area of Grodno (Belarus), Ternopil (Ukraine) and Silesia Region (Poland). Physician-diagnosed respiratory diseases and symptoms as well as allergic diseases were ascertained using the ISAAC questionnaire completed by the parents. Results In total there were 4019 children from Belarus (rural: 2018, urban: 2001), 4493 from Ukraine (1972; 2521), and 4036 from Poland (2002, 2034). The overall response rate was 76.7 %. Groups were similar in case of gender and age (p > 0.05). Almost all analyzed respiratory and allergic conditions differed significantly between countries including asthma [Poland (rural, urban): 3.5 %, 4.1 %; Ukraine: 1.4 %, 2.1 %; Belarus: 1.4 %, 1.5 %], spastic bronchitis (Poland: 2.7 %, 3.2 %; Ukraine: 7.5 %, 6.5 %; Belarus: 6.4 %, 7.9 %), and chest wheeze in the last year (Poland: 4.8 %, 5.2 %; Ukraine: 11.5 %, 13.0 %; Belarus: 10.7 %, 10.0 %). These differences remained after adjustment for potential confounders. Risk factor associations were generally similar between outcomes. Symptom characteristics of children with asthma between countries were not consistent. The ratio of current wheeze:diagnosis of asthma differed by country: (Rural areas: Belarus: 10.9:1, Ukraine: 17.3:1, Poland: 2.4:1; Urban areas: Belarus: 8.1:1, Ukraine: 7.3:1 Poland: 1.9:1). Conclusions The findings show large between-country differences and relatively low prevalence of asthma and allergic diseases in children of Western Belarus and Ukraine. There is evidence for underdiagnosis of asthma in these regions.